2008
DOI: 10.1111/j.1440-169x.2008.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Valosin‐containing protein/p97 interacts with sperm‐activating and sperm‐attracting factor (SAAF) in the ascidian egg and modulates sperm‐attracting activity

Abstract: Sperm chemotaxis toward an egg is observed in many animals, and the control of sperm-attracting activity is thought to play an important role in ensuring fertilization. However, the mechanism underlying the release of a sperm attractant from an egg is still obscure. In this study, we examined the systems involved in the release of sperm-activating and sperm-attracting factor (SAAF), which is the sperm attractant of the ascidian Ciona intestinalis. Here, we show that the egg acquires sperm-attracting activity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…These results are consistent with earlier findings that planarian small RNAs exhibit differential patterns of expression in sexual and asexual strains [10], [49]. Using RT-PCR, we verified the strain-specific expression of genes likely to play roles in sexual reproduction, and found that the gene encoding a homolog of Vcp/p97 (valosin-containing protein/p97 (CUFF.138192.0)) , which has been implicated in sexual reproduction by way of sperm-attracting activity in ascidians [56], is expressed specifically in sexual animals (Figure 2B). We also found that Smed-hnRNPA2 (CUFF.177545.0) , which encodes a homolog of hnRNPA2, and Smed-rap55 (CUFF.414275.0) , which encodes a RAP55 homolog, are much more strongly expressed in sexual animals than asexual animals (Figure 2B).…”
Section: Discussionsupporting
confidence: 87%
“…These results are consistent with earlier findings that planarian small RNAs exhibit differential patterns of expression in sexual and asexual strains [10], [49]. Using RT-PCR, we verified the strain-specific expression of genes likely to play roles in sexual reproduction, and found that the gene encoding a homolog of Vcp/p97 (valosin-containing protein/p97 (CUFF.138192.0)) , which has been implicated in sexual reproduction by way of sperm-attracting activity in ascidians [56], is expressed specifically in sexual animals (Figure 2B). We also found that Smed-hnRNPA2 (CUFF.177545.0) , which encodes a homolog of hnRNPA2, and Smed-rap55 (CUFF.414275.0) , which encodes a RAP55 homolog, are much more strongly expressed in sexual animals than asexual animals (Figure 2B).…”
Section: Discussionsupporting
confidence: 87%
“…Spermatozoa of the sea squirt Ciona intestinalis display clear chemotaxis in response to gradients of a sulfated steroid named SAAF (sperm-activating and attracting factor), which is released only from unfertilized mature oocytes (296,576,578). Since the SAAF receptor has not been identified, the signaling mechanism is not well characterized.…”
Section: B Sea Squirt (Ascidians) Spermatozoamentioning
confidence: 99%
“…After GVBD, the protein was observed in the nucleo-cytoplasmic compartment, the cytoskeletal architecture and the plasma membrane of oocytes. Similarly, p97/VCP in Ciona was reported to be localized first in the endoplasmic reticulum (ER) region and cortical region of oocytes, later in the germinal vesicle (GV) and finally in the cortical ER region after GVBD (Kondoh et al, 2008).…”
Section: Pmvcp Protein Profiles and Localization During Ovarian Develmentioning
confidence: 98%
“…Characterization of p97/VCP/ Cdc48-depleted embryos and oocytes revealed that this protein was required not only for progression of meiotic metaphase I but also for chromosome condensation at the diakinesis phase in meiotic prophase I (Sasagawa et al, 2007). Kondoh et al (2008) studied binding proteins of sperm-activating and sperm-attracting factor (SAAF) in eggs of the ascidian (Ciona intestinalis). A total of 13 SAAF-binding proteins were found in an egg plasma membrane extract and five were further analyzed by proteomic analysis: p97/VCP/Cdc48, proteasome alpha 2 subunit, MGC97756 protein, proteasome subunit Y and β-tubulin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation